Reports of Sub-Groups Constituted by The Working Group on Small Scale Industries for the 7th Plan 1985-90 Volume-II - Planning Commission (Planning Commission, 1985)
To suggest the policy framework for the development of sub scale industries taking into account the socio-economic objectives, training needs, technological and functional requirements for the Seventh Plan Period for the achieve of the objectives as well as the targets for production and employment. While doing so, the Group would specifically consider the Reports of the National Committee on the Development of Backward Areas on Industrial Organisation Industrial Dispersal and the 20 point programme.
Ministry of Industry Deptt. of Industrial Development
Ministry of Industry Deptt. of Industrial Development